Rhetorical Arts in Al-Jawahiri’s Poetry in Critical Discourse - Ayoob Ali Othman; Jalil Hassan Muhamad (Zanco Journal of Humanity Sciences)
This research deals with an aspect of the rhetorical arts in Al-Jawahiri’s poetry in critical discourse. His poetry was the subject of research, study, and criticism throughout the seventy years of his creative experience. Critics and researchers studied and criticized his poetry according to the different rhetorical arts.